ANALISIS EFISIENSI RANTAI PASOK CABAI RAWIT (CAPSICUM FRUTESCENS L.) KABUPATEN GOWA DI ERA PANDEMI COVID-19 - Kamilia Nur Yaumil Ali; Mahyuddin Mahyuddin; Letty Fudjaja (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
The COVID-19 pandemic that hit almost all agricultural sectors also hit horticultural commodities, one of which was cayenne pepper in Gowa Regency where the process of distributing chili peppers was often hampered due to the government's policy of restricting social activities. This indicates that there is a problem with the cayenne pepper agribusiness system in Gowa Regency, although it has not been identified. Therefore, it is important to analyze the efficiency of the cayenne pepper supply chain during the COVID-19 pandemic in Gowa Regency. This study aims to analyze the efficiency of each channel of the cayenne pepper supply chain in Gowa Regency in the era of the covid-19 pandemic. This study uses marketing margin analysis and farmer's share analysis. The results of this study indicate that the cayenne pepper supply chain in Gowa Regency during the COVID-19 pandemic generally runs efficiently where the most efficient channels are channel 1 and channel 2.